Exceptionally Ductile and Tough Biomimetic Artificial Nacre with Gas Barrier Function. Issue 32 (26th June 2018) - Eckert, Alexander; Rudolph, Tobias; Guo, Jiaqi; Mang, Thomas; Walther, Andreas
Abstract: Synthetic mimics of natural high‐performance structural materials have shown great and partly unforeseen opportunities for the design of multifunctional materials. For nacre‐mimetic nanocomposites, it has remained extraordinarily challenging to make ductile materials with high stretchability at high fractions of reinforcements, which is however of crucial importance for flexible barrier materials. Here, highly ductile and tough nacre‐mimetic nanocomposites are presented, by implementing weak, but many hydrogen bonds in a ternary nacre‐mimetic system consisting of two polymers (poly(vinyl amine) and poly(vinyl alcohol)) and natural nanoclay (montmorillonite) to provide efficient energy dissipation and slippage at high nanoclay content (50 wt%). Tailored interactions enable exceptional combinations of ductility (close to 50% strain) and toughness (up to 27.5 MJ m −3 ). Extensive stress whitening, a clear sign of high internal dynamics at high internal cohesion, can be observed during mechanical deformation, and the materials can be folded like paper into origami planes without fracture. Overall, the new levels of ductility and toughness are unprecedented in highly reinforced bioinspired nanocomposites and are of critical importance to future applications, e.g., as barrier materials needed for encapsulation and as a printing substrate for flexible organic electronics. Abstract : Simple solution casting of two hydrogen‐bonding polymers and natural nanoclay allows the preparation of ternary nacre‐mimetic systems with unprecedented toughness and ductility enabled by many, but weak hydrogen bonds. The approach serves as a gateway to realize real‐life application of functional nacre‐mimetics with ductile and fracture‐resistant behavior, combined with an excellent gas barrier.